Evaluation of the Challenges of Implementing Sustainability and ESG Principles in Modern Corporate Financial Reporting - Herry Adi Setya Wibowo; Ismail Noy; Entar Sutisman (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to evaluate companies' challenges in implementing ESG (Environmental, Social, and Governance) principles in modern corporate financial reporting. It seeks to address critical questions about the primary obstacles to ESG adoption and strategies to overcome them, enhancing the effectiveness and reliability of reporting practices. Research Method: A qualitative systematic literature review synthesized findings from recent academic and industry publications. This approach comprehensively examined the existing literature on ESG implementation, highlighting key challenges and potential solutions. The methodology focused on identifying patterns, comparing global practices, and linking theoretical frameworks with practical implications. Results and Discussion: The study found significant challenges, including inconsistent ESG reporting standards, internal company resistance, and limitations in human and technological resources. It revealed that successful integration requires active stakeholder engagement, continuous training, and leveraging advanced technology for effective data management. The research also highlighted discrepancies in the adoption of ESG practices between developed and developing regions, noting that more robust regulatory frameworks in places like Europe facilitate better implementation than in regions facing regulatory and resource constraints. The findings emphasized the relevance of stakeholder theory in promoting transparency and accountability and the importance of fostering a culture that supports sustainability. Implications: The study contributes to academic knowledge by expanding on existing theories and linking them to practical strategies for ESG implementation. For managers and policymakers, the research offers insights into designing adaptive frameworks and practices that cater to local and global contexts. Future research should include empirical studies to validate these findings and explore region-specific challenges for deeper practical insights.